2020
DOI: 10.2147/dddt.s228751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effects of Chlorogenic Acid on Cerebral Ischemia/Reperfusion Injury Rats by Regulating Oxidative Stress-Related Nrf2 Pathway</p>

Abstract: Introduction: Cerebral ischemia-reperfusion (CI/R) injury is caused by blood flow recovery after ischemic stroke. Chlorogenic acid (CGA, 5-O-caffeoylquinic acid) is a major polyphenol component of Coffea canephora, Coffea arabica L. and Mate (Ilex paraguariensis A. StHil.). Previous studies have shown that CGA has a significant neuroprotective effect and can improve global CI/R injury. However, the underlying molecular mechanism of CGA in CI/R injury has not been fully revealed. Materials: In this study, CI/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 42 publications
(41 reference statements)
4
98
0
2
Order By: Relevance
“…Also, another study in a rat model of cerebral ischemia (CI) demonstrated that 5‐CQA reduces brain injury, brain edema, sensory‐motor functional deficits, and BBB damage by enhancing free‐radical scavenging activity and inhibiting interstitial collagenase (MMP1) and 72 kDa type IV collagenase (MMP2) (Lee et al., 2012). Furthermore, a recent study showed that 5‐CQA reduces brain damage, nerve damage, and volume of cerebral infarction and neuronal apoptosis by regulating the NFE2L2 signaling pathway in CI‐reperfusion (CI/R)‐induced oxidative stress in rats (Liu, Wang, Zhang, & Zhang, 2020). According to Hermawati, Arfian, Mustofa, and Partadiredja (2020), 5‐CQA improved spatial memory and prevented the degeneration of hippocampal CA1 pyramidal cells in CI/R rats, which may be attributed to increased expression of Bcl2 , platelet endothelial cell adhesion molecule ( Pecam1 , also known as Cd31 ), and superoxide dismutase [Mn], mitochondrial ( Sod2 ), as well as the suppression of the expression of endothelin‐1 ( Edn1 , also known as Et‐1 ).…”
Section: Beneficial Properties For Healthmentioning
confidence: 99%
“…Also, another study in a rat model of cerebral ischemia (CI) demonstrated that 5‐CQA reduces brain injury, brain edema, sensory‐motor functional deficits, and BBB damage by enhancing free‐radical scavenging activity and inhibiting interstitial collagenase (MMP1) and 72 kDa type IV collagenase (MMP2) (Lee et al., 2012). Furthermore, a recent study showed that 5‐CQA reduces brain damage, nerve damage, and volume of cerebral infarction and neuronal apoptosis by regulating the NFE2L2 signaling pathway in CI‐reperfusion (CI/R)‐induced oxidative stress in rats (Liu, Wang, Zhang, & Zhang, 2020). According to Hermawati, Arfian, Mustofa, and Partadiredja (2020), 5‐CQA improved spatial memory and prevented the degeneration of hippocampal CA1 pyramidal cells in CI/R rats, which may be attributed to increased expression of Bcl2 , platelet endothelial cell adhesion molecule ( Pecam1 , also known as Cd31 ), and superoxide dismutase [Mn], mitochondrial ( Sod2 ), as well as the suppression of the expression of endothelin‐1 ( Edn1 , also known as Et‐1 ).…”
Section: Beneficial Properties For Healthmentioning
confidence: 99%
“…Chlorogenic acid was also reported to ameliorate brain ischemia-induced injury in rodents. In models of cerebral ischemia/reperfusion injury, it significantly reduced mortality [ 314 ], improved neurological deficit scores [ 314 , 315 ], attenuated sensory-motor functional deficits [ 316 ], reduced infarct volume [ 314 , 315 , 316 , 317 ], suppressed CA1 pyramidal cell loss [ 318 , 319 , 320 ], decreased brain edema [ 315 , 316 , 317 ], and attenuated blood–brain barrier (BBB) damage [ 316 , 317 ]. Importantly, it was demonstrated that chlorogenic acid has a neuroprotective effect against ischemia-induced cognitive deficits.…”
Section: Neuroprotective Effects Of Coffee Bioactive Compoundsmentioning
confidence: 99%
“…Chlorogenic acid, the major polyphenolic compound in coffee, has a neuroprotective effect against cerebral ischemia/reperfusion (CI/R) rats by activating the Nrf2 pathway and inducing NQO1 and HO-1 expression [ 149 ]. Furthermore, lyciumamide A from wolfberry can prevent CI/RI by activating the PKC/Nrf2/HO-1 signaling pathway, thereby ameliorating oxidative damage and attenuating neuronal apoptosis [ 150 ].…”
Section: Nrf2 Signaling Pathway and Cerebrovascular Disease (Cd)mentioning
confidence: 99%